1987
DOI: 10.1901/jeab.1987.47-363
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Tolerance: Acute Versus Chronic Effects as Dependent Upon Fixed‐ratio Size

Abstract: The effects of cocaine on operant behavior were studied by examining fixed-ratio value as a factor in the development of tolerance. Pigeons pecked a response key under a three-component multiple schedule, with each bird being exposed to fixed-ratio values that were categorized as small, medium, or large. Administered acutely, cocaine (1.0 to 10.0 mg/kg) produced dose-related decreases in overall rate of responding. Responding maintained by the largest ratio was decreased by lower doses than those required to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
74
5

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 23 publications
16
74
5
Order By: Relevance
“…Galizio The stimulation of avoidance behavior and responding maintained at relatively low rates by VI schedules of timeout from avoidance may be seen as largely consistent with the literature on the effects of cocaine on schedulecontrolled behavior. However, the large increases in rates maintained by VR schedules of timeout from avoidance-were inconsistent with previous studies of the effects of cocaine on food-reinforced behavior maintained by ratio schedules that found only decreases in, rate (Hoffman, Branch, & Sizemore, 1987;Hughes & Branch, 1991;Shelnutt et al, 1992;Smith, 1990;Spealman et al, 1979). In the present study, cocaine not only increased behavior maintained under ratio contingencies, but in many cases increased it as much or more than lower rate behavior maintained under Sidman avoidance or VI schedules.…”
Section: Discussioncontrasting
confidence: 80%
“…Galizio The stimulation of avoidance behavior and responding maintained at relatively low rates by VI schedules of timeout from avoidance may be seen as largely consistent with the literature on the effects of cocaine on schedulecontrolled behavior. However, the large increases in rates maintained by VR schedules of timeout from avoidance-were inconsistent with previous studies of the effects of cocaine on food-reinforced behavior maintained by ratio schedules that found only decreases in, rate (Hoffman, Branch, & Sizemore, 1987;Hughes & Branch, 1991;Shelnutt et al, 1992;Smith, 1990;Spealman et al, 1979). In the present study, cocaine not only increased behavior maintained under ratio contingencies, but in many cases increased it as much or more than lower rate behavior maintained under Sidman avoidance or VI schedules.…”
Section: Discussioncontrasting
confidence: 80%
“…Thus, the differences in drug-induced decrements in reinforcement rate do not appear to provide an adequate account of the results obtained. The reasons why the findings of Schuster et al (1966) do not pertain are unclear, but are not unprecedented (Hoffman, Branch, & Sizemore, 1987). Perhaps other procedural aspects of the study, including the instructions engendering the behavior, may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers (e.g., Egli et al, 1992;Harper, 1999aHarper, , 1999bHoffman et al, 1987;Poling et al, 2000;Yoo et al, 2003) have obtained results consistent with behavioral momentum theory with drugs from several pharmacological classes such as stimulant (e.g., cocaine), antipsychotic (e.g., haloperidol), and opioid (e.g., morphine), others have found that pharmacological disruptors do not operate in the same manner as non-pharmacological disruptors (e.g., Cohen, 1986;JimenezGomez and Shahan, 2007;Lamb and Ginsburg, 2005;Pinkston et al, 2009). For example, Cohen (Experiment 3) investigated resistance of food-maintained responses by rats to damphetamine, sodium pentobarbital, haloperidol, and cholecystokinin, and found that behavior was not necessarily more resistant to disruptive effects of these drugs in the component with higher reinforcement rates.…”
Section: Introductionmentioning
confidence: 99%